2008
DOI: 10.14411/eje.2008.038
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the spermatheca in the Cydnidae (Hemiptera: Heteroptera): Bearing of its diversity on classification and phylogeny

Abstract: Abstract. Cuticular parts of the spermatheca and associated vaginal structures (chiefly the ring sclerites of the parietovaginal glands) have been examined and compared in 190 cydnid species representing 65 genera and all five subfamilies currently recognized in the family (Amnestinae, Cephalocteinae, Cydninae, Garsauriinae, Sehirinae). Four species belonging to genera formerly included within the Cydnidae (Dismegistus, Parastrachia, Thaumastella, Thyreocoris) were also examined. Morphology of the three main p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 45 publications
4
50
0
Order By: Relevance
“…Most importantly, our results are in contrast with all previous findings based on the morphological characters. The close relationship between the Parastrachiidae and the genus Sehirus shown in our study was also indicated in other morphological investigations (Miyamoto, 1961;Dolling, 1981;Lis, 2002;Lis and Schaefer, 2005;Grazia et al, 2008;Pluot-Sigwalt and Lis, 2008;Matesco et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Most importantly, our results are in contrast with all previous findings based on the morphological characters. The close relationship between the Parastrachiidae and the genus Sehirus shown in our study was also indicated in other morphological investigations (Miyamoto, 1961;Dolling, 1981;Lis, 2002;Lis and Schaefer, 2005;Grazia et al, 2008;Pluot-Sigwalt and Lis, 2008;Matesco et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The monophyly of the Cydnidae and phylogenetic relationships with other pentatomoid families are still controversial (Grazia et al 2008 ;Pluot-Sigwalt and Lis 2008 ;Lis 2010 ). Two of the typical characteristics of the Cydnidae (i.e., coxal combs and spinose tibiae) are shared with the related families Parastrachiidae, Thaumastellidae, and Thyreocoridae, sometimes included as subfamilies in a more inclusive taxon (Dolling 1981 ;Schuh and Slater 1995 ).…”
Section: Classifi Cation and Diversitymentioning
confidence: 99%
“…It includes more than 750 species in 93 genera, divided in six subfamilies (Table 21.1 ) (Grazia et al 2008 ;Pluot-Sigwalt and Lis 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even if the monophyly and the delimitation of family Cydnidae has been questioned recently (Grazia et al 2008;Pluot-Sigwalt and Lis, 2008), these insects are undoubtedly closely related to the Pentatomidae. To such an extent that they were classifi ed as a subfamily of the Pentatomidae in early literature.…”
Section: Introductionmentioning
confidence: 99%
“…Th e classifi cation of subfamilies and tribes follows in part Froeschner (1960), Lis (1994Lis ( , 1999Lis ( , 2006 and Pluot-Sigwalt and Lis (2008).…”
Section: Introductionmentioning
confidence: 99%